Analisis Kontribusi Penerimaan Pajak Kendaraan Bermotor (PKB) Dalam Meningkatan Pendapatan Daerah Provinsi Jawa Barat Tahun 2017-2021 - Riri Rumaizha; Gusmirza Bunga Pertiwi (LPPM POLITEKNIK LP3I BANDUNG, 2024)
The aim of this final assignment is to investigate the contribution of motor vehicle tax to the Regional Original Income (PAD) of West Java Province, specifically in the Samsat PPPD Bandung City III Soekarno Hatta Region. The research method used is the Quantitative Descriptive method. It aims to explain or describe the state of West Java Province's PAD regarding motor vehicle income, identify obstacles experienced in collecting motor vehicle collections, and propose solutions to increase regional income in West Java province. The data used in the analysis of Motor Vehicle Tax Revenue (PKB) and its impact on the Original Regional Income of Java Province was obtained through evaluations, interviews, and the author's internship at the Samsat Office. After careful analysis and discussion, it was concluded that there are still issues with motor vehicle tax revenue in the East Bandung Samsat and West Java PAD. It is hoped that this analysis will be useful in the future.